Marine Propulsion System - AL SHARIF, HANAN AHMED (2017)
The research is an application of a multivariable system control for marine propulsion system where the propeller pitch is controlled to reach stability within different conditions and disturbances. Attention is paid also in fuel consumption in order to reduce the pollution via environment and cost reduction by improving the engine speed control. This dissertation is done on the marine propulsion system model that has been solved mathematically first and then testing the stability of the model using MATLAB/ SIMULINK software. By modeling the ship propulsion system it becomes easier to understand, what parameters are affecting the system and how to control them. The first part of the research is about an introduction of the marine propulsion system. The research problem states a model of multivariable control system for a propeller pitch with two inputs and three outputs. These are the fuel flow rate and the cylinder area controlling the torque and thrust that affects the ship speeds. The method used in this controller is the least effort technique as from the previous control dissertation this method is producing maximum stability, producing best performance and acting as best method for disturbance recovery. As mentioned above and concludes in this research after simulating the model, the least effort control technique shows the best performance and disturbance recovery using the simplest controller. These are the reasons of implementing it in many applications at the main time and the marine propulsion system a good example of the least effort technique application.